Implementasi Pembelajaran Berdiferensiasi untuk Memenuhi Kebutuhan Belajar Siswa yang Beragam - Koimah, Siti Mariyatul; Zahra, Nur Amalia; Prasitini, Endang; Sasmita, Saepudin Karta; Sari, NurulLita (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
Differentiated instruction is an approach focused on adapting teaching methods, content, processes, and learning environments to meet the diverse needs, interests, and abilities of individual students. This study aims to analyze the implementation of differentiated instruction as a solution to address the diversity of student characteristics in the classroom. Using a systematic literature review, this research examines various strategies and challenges faced in applying this approach in primary and secondary education. The findings reveal that differentiated instruction enhances student engagement, learning outcomes, and fosters character development and independence. However, successful implementation requires full support from schools, sufficient resources, and adequate training for educators. The study concludes that differentiated instruction is an effective approach to creating inclusive and responsive learning experiences that cater to diverse student needs.